Transdermal delivery of nobiletin using ionic liquids - Tadashi Hattori (Nature Portfolio, 2019)
Abstract Nobiletin (NOB), a flavonoid, has extremely low water solubility and low oral bioavailability; however, despite these problems, various physiological effects have been investigated in vitro. In the present study, we investigated the transdermal delivery of NOB using choline and geranic acid (CAGE), which is a biocompatible material that has been reported to be a promising transdermal delivery approach. The feasibility was evaluated by a set of in vitro and in vivo tests. A solubility evaluation demonstrated that CAGE induced excellent solubility of NOB induced by multipoint hydrogen bonding between NOB and CAGE. In vitro transdermal tests using a Franz diffusion cell showed that CAGE was effective in enhancing transdermal absorption of NOB, compared to other penetration enhancers. Subsequent in vivo tests demonstrated that CAGE significantly improved area under the concentration-time curve of NOB in vivo and NOB/CAGE sample showed 20-times higher bioavailability than oral administration of NOB crystal. Furthermore, NOB/CAGE sample also showed significant drops of the blood glucose level in rats derived from hypoglycemic activity of NOB. Thus, transdermal administration of NOB using CAGE was shown to be feasible, which indicates that the use of CAGE may be adapted for other flavonoids that also show both low water solubility and low permeability.